42.4 WHITE MATTER CONNECTIVITY ABNORMALITIES AND AUDITORY HALLUCINATIONS IN FIRST EPISODE PSYCHOSIS. (9th April 2019) - Salisbury, Dean; Wang, Yiming; Yeh, Frank; Coffman, Brian
Abstract: Background: Functional MRI work, particularly of Hoffman and colleagues, identified cortical hubs related to auditory hallucinations (AH) in schizophrenia, including left-hemisphere Broca's and Wernicke's areas and the putamen. In addition, over-activity in auditory cortices may also play a role in AH. How structural pathology in white matter tracts connecting the fMRI hubs related to AH is unknown, as is the presence of white matter pathology in these tracts in early psychosis. Methods: We examined white matter connectivity among these hub areas using diffusion spectrum imaging (DSI) in 40 first-episode psychosis (FEP) and 32 matched healthy comparison subjects (HC). Our primary measure was generalized fractional anisotropy (gFA), the DSI analogue of FA reported in studies using diffusion tensor imaging (DTI). Results: Across the auditory transcallosal (ATC) fibers, groups did not differ in gFA. However, AVH+ FEP (n =23) had reduced gFA within the ATC compared to AVH- FEP (n =17, p =.009). For left and for right arcuate fasciculus (AF) fibers, there were no significant group differences in gFA. However, AH+ FEP had reduced gFA within the left hemisphere AF compared to AH- FEP (p =.040). By contrast, AH+ FEP and AH- FEP did not differ in right hemisphere AF gFA (p =.31). For left Broca's to putamen fibers, FEP showed reduced overall gFA (p =.038), but not in the right hemisphere (p =.37). AH+ FEP showed reduced left Broca's to putamen gFA compared to AVH- FEP (p =.046). AH+ and AH- FEP did not differ in right Broca's to putamen gFA. Overall FEP did not show gFA reductions compared to HC in left hemisphere Wernicke's to putamen gFA (p =.62), but AH+ showed reductions relative to AV- (p =.049). Finally, the FEP group overall showed trend-level reductions in gFA between right Wernicke's and putamen (p =.076), with AH+ individuals reduced in relation to AH- individuals (p =.026). Conclusions: While the overall FEP group generally did not show white matter structural connectivity abnormalities in the left hemisphere cortical-subcortical language circuit and inter-hemispheric auditory fibers, FEP with AH were reduced, particularly in the left hemisphere. Although the precise microstructural abnormality giving rise to gFA reductions is unknown, it is thought to indicate more "leaky" axons and is likely manifest in slowed conduction times. Thus, at the first psychotic episode, AH is associated with impaired left-language system cortico-cortical, cortico-subcortical, and inter-hemispheric auditory communication, likely reflecting mistiming of information flow between language-related cortical centers.